The U.S.-Guatemala Remittance Corridor : Understanding Better the Drivers of Remittances Intermediation - Cheikhrouhou, Hela; Jarque, Rodrigo; Hernández-Coss, Raúl; El-Swaify, Radwa (Washington, DC: World Bank, 2012)
This study reports on recent development and future potential for U.S.-based Guatemalan workers cross-border retail transfers to be more formal, cheaper, and disposed to the cross-sale of financial products and services. It also presents the key features of remittances senders, recipients, instruments, and intermediaries involved. The paper focuses on three areas: (a) the main characteristics of the Guatemalan migrants in the United States and the key drivers behind their decision to remit money and to choose an intermediary; (b) financial infrastructure supporting U.S.-Guatemala remittances processing, especially the role of technology, payment systems and innovations going forward, as avenues to help lower transaction costs, among others; and (c) the landscape of workers remittances distribution in Guatemala, examines the characteristics of recipients and the evidence of remittances impact, and analyzes the indications of potential for cross-sale of financial services to recipients.